Insights into the biosynthesis of septacidin l-heptosamine moiety unveils a VOC family sugar epimerase - Meng Chen; Zhengyan Guo; Jinyuan Sun; Wei Tang; Min Wang; Yue Tang; Pengwei Li; Bian Wu; Yihua Chen (Elsevier, 2023)
l-Heptopyranoses are important components of bacterial polysaccharides and biological active secondary metabolites like septacidin (SEP), which represents a group of nucleoside antibiotics with antitumor, antifungal, and pain-relief activities. However, little is known about the formation mechanisms of those l-heptose moieties. In this study, we deciphered the biosynthetic pathway of the l,l-gluco-heptosamine moiety in SEPs by functional characterizing four genes and proposed that SepI initiates the process by oxidizing the 4'-hydroxyl of l-glycero-α-d-manno-heptose moiety of SEP-328 (2) to a keto group. Subsequently, SepJ (C5 epimerase) and SepA (C3 epimerase) shape the 4'-keto-l-heptopyranose moiety by sequential epimerization reactions. At the last step, an aminotransferase SepG installs the 4'-amino group of the l,l-gluco-heptosamine moiety to generate SEP-327 (3). An interesting phenomenon is that the SEP intermediates with 4'-keto-l-heptopyranose moieties exist as special bicyclic sugars with hemiacetal-hemiketal structures. Notably, l-pyranose is usually converted from d-pyranose by bifunctional C3/C5 epimerase. SepA is an unprecedented monofunctional l-pyranose C3 epimerase. Further in silico and experimental studies revealed that it represents an overlooked metal dependent-sugar epimerase family bearing vicinal oxygen chelate (VOC) architecture.